2017
DOI: 10.1016/j.ijpsycho.2017.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Heritability of brain activity related to response inhibition: A longitudinal genetic study in adolescent twins

Abstract: The ability to inhibit prepotent but context- or goal-inappropriate responses is essential for adaptive self-regulation of behavior. Deficits in response inhibition, a key component of impulsivity, have been implicated as a core dysfunction in a range of neuropsychiatric disorders such as ADHD and addictions. Identification of genetically transmitted variation in the neural underpinnings of response inhibition can help to elucidate etiological pathways to these disorders and establish the links between genes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 87 publications
0
17
0
Order By: Relevance
“…The ERP P3 component, a positive component occurring around 300–800 ms post-stimulus, is typically associated with late general inhibition [ 50 , 51 ] and attentional resource allocation [ 68 , 69 ]. Several experimental studies have generally demonstrated increased amplitude and shortened latency of P3 components in relation to cognitive electrophysiological improvements caused by an acute bout of exercise [ 70 , 71 , 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…The ERP P3 component, a positive component occurring around 300–800 ms post-stimulus, is typically associated with late general inhibition [ 50 , 51 ] and attentional resource allocation [ 68 , 69 ]. Several experimental studies have generally demonstrated increased amplitude and shortened latency of P3 components in relation to cognitive electrophysiological improvements caused by an acute bout of exercise [ 70 , 71 , 72 ].…”
Section: Discussionmentioning
confidence: 99%
“… 204 Similarly, the heritability of ERPs elicited in a Go/No-Go-task measuring response inhibition known to be altered in ADHD, was found to be significantly heritable. 205 …”
Section: Current Neurobiological and Neuropsychological Conceptsmentioning
confidence: 99%
“…The phenotypic correlations associated with a rg of .40, and h 2 ERP = .40 would be .26, which is way above what we observe in this sample. With this caveat in mind, we first estimated the heritability of key ERPs derived from the flanked CPT in an early adolescence, as previous studies focused mainly on late adolescence [49] and adulthood [47,48]. We found significant MZ cross-twin within-trait correlations for all ERPs (Table 3) which support the presence of genetic influences.…”
Section: Discussionmentioning
confidence: 64%
“…More fundamentally, a trait measure that is a candidate genetic-risk index must also be heritable in itself [45,46]. Data in adults (ages 18–28) point towards heritabilities of ~.50–60 for P3 and N2 amplitudes [47], with such magnitudes staying relatively stable across adulthood (ages 17–23) [48] and across early adolescence (ages 12–16) [49]. There is also evidence for the heritability of CNV in delayed response tasks (with estimates between ~.21 to ~.43, varying depending on task-load conditions and the channels considered; [50]).…”
Section: Introductionmentioning
confidence: 99%